Comprehensive Analysis of Circular RNAs to Decipher the Potential Roles in Blind-Side Hypermelanosis in Chinese Tongue Sole (Cynoglossus semilaevis) - Hu, Yuanri; Li, Yangzhen; Cheng, Peng; Chen, Songlin (Frontiers in Marine Science, 2022)
Blind-side hypermelanosis is an emerging concern across the flatfish aquaculture industry including Chinese tongue sole (Cynoglossus semilaevis). Circular RNAs (circRNAs) as endogenous non-coding RNAs have been acknowledged playing important roles in various biological processes. However, the underlying regulatory mechanisms of circRNAs involved in flatfish blind-side hypermelanosis remain unclear. In this study, to profile the circRNA expression pattern and circRNA-microRNA-messenger RNA (mRNA) network, high-throughput sequencing was performed by using blind-side normal and hypermelanotic skins of tongue sole. A total of 73 differentially expressed circRNAs were identified and the competing endogenous RNA (ceRNA) network was constructed. Further, circRNA host genes and mRNAs involved in ceRNA network were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment analyses. Several GO terms and pathways of biological significance were identified and well addressed the generation of blind-side hypermelanosis to some extent. These interesting results extend the understanding of the functional profile of circRNAs and yield valuable insights into the molecular regulatory mechanisms of hypermelanosis in flatfish.